Mechanical Considerations of Bioprinted Tissue - Strobel, Hannah A.; Moss, Sarah M.; Hoying, James B. (Frontiers in Mechanical Engineering, 2020)
Bioprinting enables the fabrication of engineered tissues with complex features and is conducive to automated tissue manufacturing and scale up. As cell systems and tissues are dynamic and very responsive to environmental cues, including biomechanical stimuli, the form and function of bioprinted tissues can change dramatically after printing. Here, we discuss tissue biomechanics relevant to printed cell systems and tissues emphasizing the dynamic and complex relationship between cell behavior, matrix deposition, and tissue forces. Furthermore, we provide perspectives on the control and manipulation of mechanical forces and designed boundary conditions for tissue constructs in printing-based approaches and strategies.